Protocol for Heterologous Expression of Insect Odourant Receptors in Drosophila - Gonzalez, Francisco; Witzgall, Peter; Walker, William B. (Frontiers in Ecology and Evolution, 2016)
Insect olfactory receptors (ORs) are tuned to volatile chemicals, they are expressed in the membrane of olfactory sensory neurons (OSNs), housed in sensilla on the antenna. The olfactory apparatus is under strong selection and ORs are tuned to vital chemical signals, mediating social communication, feeding and oviposition, and avoidance of predators and pathogens. An emerging technique to reliably and efficiently identify the key ligands of ORs is to express single ORs in heterologous cell systems for subsequent screening. Several in vivo and in vitro platforms have been developed; we here provide a step-by-step protocol for OR expression in Drosophila melanogaster OSNs. Following RNA extraction, molecular cloning of ORs and injection of plasmid vectors into Drosophila embryos to create flies with OR transgenes, single ORs are expressed, via crossing with specific transgene promoters in OSNs of ab3 and T1 antennal sensilla. This approach enables replicable single sensillum electrophysiological recordings (SSR) from readily distinguishable Drosophila sensilla, containing OSNs expressing transgenic ORs. We expect this method to be applicable to ORs across insect orders and to increasingly contribute to chemical ecology research. Heterologous expression enables thorough investigation of single ORs, towards the identification of yet unknown, behaviourally and ecologically relevant chemical signals. It also enables investigations of the functional properties of ORs and their evolutionary diversification, through comparative structure-activity studies across phylogenies.